Desenvolvimento e validação de um agente conversacional para apoiar a prática de vigilância alimentar e nutricional na atenção primária à saúde - Battisti, Eliza Sella (2023)
Food and Nutritional Surveillance contributes to the planning of nutritional care in Primary Health Care. In this context, investing in the qualification of professionals and managers in this area, as well as in innovations in health, becomes an obvious need, since training is insufficient and many barriers are encountered in its implementation. In this way, innovations in health refer to the insertion and adhesion of new processes, products, practices, programs or policies developed in order to meet a real difficulty and that refers to bringing significant advantages to individuals, groups, societies or organizations. An example of an innovative resource is conversational interaction, which can contribute to the training of human resources in health. The objective of this study was to propose the development of an interactive conversational agent or chatbot to support the practice of food and nutrition surveillance in primary health care by health professionals. This is a study with technological development, with a mixed approach, which took place in three phases: mapping of barriers and difficulties in the practice of food and nutrition surveillance, development of a chatbot through participatory design and validation of content and analysis of the experience of the user with a panel of experts. The final version was organized and programmed to respond to variations of 60 intentions or keywords about food and nutrition surveillance, according to the content already validated by specialists and structured by the development team. Content validation was carried out by seven specialists through an online questionnaire, and the Global Content Validation Index of 0.88 was obtained, which is considered a favorable index. Regarding the user experience analysis, four subcategories were listed regarding their positive aspect (attractiveness, ease and practicality of use, clear and enriching content) and two related to negative points (difficulty of use and complexity of information). Thus, 82.6% of the experts' speeches were positive, while 17.4% highlighted negative aspects of the experience. The virtual assistant of the Food and Nutrition Surveillance Observatory was developed and can now be used as a powerful and innovative resource in strengthening nutrition and public health. It is believed that this tool can support the practice of Food and Nutrition Surveillance in Primary Health Care and facilitate its implementation, clarifying doubts and providing relevant information. This work is expected to qualify nutritional care through an innovative, interactive, educational, continuous, accessible and reliable technology. Future work will involve evaluating the experience of health professionals when interacting with the chatbot and its impact on the practice of Food and Nutritional Surveillance.